2017
DOI: 10.3390/su9091634
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Eco-Efficiency Measurement, Characteristics, and Its Influence Factors in China

Abstract: Abstract:As an emerging field of eco-efficiency, tourism eco-efficiency is becoming an important way to measure the sustainable development of tourism. This study calculated and decomposed tourism CO 2 emissions in China, explored its evolution and distribution characteristics by using the ratio method of tourism eco-efficiency, and analyzed the influencing factors by adopting a regression model. The results indicate that: (1) tourism CO 2 emissions in China have increased significantly, their largest source i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 48 publications
6
33
1
Order By: Relevance
“…Our results indicate that the growth of tourism sector is an important factor that can significantly control the CO 2 emission and promote the green economy in Xinjiang. Our findings are similar with the results of Qiu et al [31] stated that tourism is a significant contributor of carbon emission in China and the emission level increased continuously. The impact of tourism on environment and its intensity is different for various parts of China.…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicate that the growth of tourism sector is an important factor that can significantly control the CO 2 emission and promote the green economy in Xinjiang. Our findings are similar with the results of Qiu et al [31] stated that tourism is a significant contributor of carbon emission in China and the emission level increased continuously. The impact of tourism on environment and its intensity is different for various parts of China.…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
“…Qiu et al [31] calculated and decomposed the tourism and CO 2 link for China and found that tourism is a significant contributor of carbon emission in China and the emission level increased continuously. Several factors including tourism are responsible for huge consumption, but transportation stands at the top.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies complying with environmental regulations can foster technological progress; enhance the efficiency of their use of resources; minimize economic loss; improve their image; promote green process innovation; become more innovative; attract clients, investors, and potential partners; and improve relations with the government and other institutions. Additionally, they have a more consolidated business strategy focused on environmental care (Qiu, Fang, Yang, & Zhu, 2017; Qiu, Hu, & Wang, 2020; Zhang, Liang, Feng, Yuan, & Jiang, 2020). The purpose of complying with the law is to apply environmental strategies in order to ameliorate environmental damage.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hence, Tang et al (2014) have found that, given the considerable increases in total emissions during 1990-2012, transportation sector generates 80% of the emission and the aggregate economic contribution of tourism sector and tourist travels are significantly higher than compared to their contribution to total CO 2 emissions. When attempting to quantify the impact of direct and indirect CO 2 emissions associated to tourism activities in China, Meng et al (2016), Zhang and Gao (2016), Qiu et al (2017) consider that tourism and travel have contributed to both economic growth and increase of CO 2 emissions, but to a much lesser extent as compared to other industry sectors; in the same time, the authors point out that the results are mixed at regional level. However, researchers agree that in large cities, pollution has a negative effect on tourism development.…”
Section: The Environment-tourism Relationship: the Asymmetry Of Consequencesmentioning
confidence: 99%